Geospatial analysis enables combined poultry–fish farm monitoring in the fragile state of Myanmar - Belton, Ben; Fang, Peixun; Liu, Shuo; Zhang, Kaifeng; Zhang, Xiaobo (Springer, 2025)
Food security is challenging to measure in fragile contexts. Here we combine data from previous field surveys with remotely sensed images and apply deep-learning techniques to estimate changes in the number and area of chicken houses on integrated chicken–fish farms and the supply of chicken meat and eggs from 2010 to 2023 in Yangon region, Myanmar. Yangon’s poultry sector grew ~10% annually from 2010 to 2020 but contracted ~8% annually from 2020 to 2023.